Eight Javanese teaching issues and its possible solutions: A systematic literature review - Ardika Adiputra Ramadhansyah; Mulyana Mulyana; Tri Ulfa; Miftakhuddin Miftakhuddin (Yayasan Keluarga Guru Mandiri, 2022)
Previous research to diagnose problems in Javanese language teaching was not well organized. As a result, there was no adequate formulation of recommendations for educational policies. This research was conducted to overcome this weakness. Thus the objectives of this research were: (a) to reveal trends in Javanese language teaching problems in the last 10 years, (b) to explain the causes of these problems, and (c) to develop recommendations for solving the problems. Using literature review design, this research examines 32 empirical studies on the problem of teaching Javanese. The literature that meets the criteria is analyzed thematically-qualitatively. The findings of this research reveal three categories of problems, namely: managerial, individual-social, and instructional. By tracing the sequences, the causes of the series of trouble are the managerial problem, such as curriculum design, teacher competencies, and the quality of teaching materials. Curriculum design issues, for example, affect minimum standards of achievement. Likewise, the problem of teacher competence affects the use of methods and media selection, which has an impact on motivation, attention, and learning achievement. This prevalence occurred in almost all research locations (Central Java, Special Region of Yogyakarta, and East Java). Especially in Central Java and East Java, individual-social issues are also very influential concerning students' dialect, culture, and ethnicity. In conclusion, complexity of Javanese teaching issues in the last 10 years come from managerial aspect. As part of the conclusion, this research presents academic contribution for scholars and stakeholders by proposing four eligible recommendations related to the development of teacher competencies and the granting of authority to developers of teaching materials (and curriculum) at a lower level.